Macro element contents of different genotype cows’ milk - Hódi, Katalin; Szendrei, Zoltán; Kovács, Béla; Holcvart, Mária; Béri, Béla (Acta Agraria Debreceniensis, 2010)
The level of mineral elements is important factor regarding the quality of milk. The aim of our research study was to determine the content of mineral elements in milk of Holstein, Jersey, Brown Swiss, Ayrshire, Norwegian-red, Swedish-red cows in the first stage of lactation. All cows were fed with the same type (composition) of feed and they were kept under the same condition. The concentration of macroelements (K, Na, Ca, P, Mg, S) in digested milk samples was determined by inductively coupled plasma optical emission spectrometry (ICP-OES).